2022
DOI: 10.3389/fphys.2021.753833
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Liver Sinusoidal Endothelial Cells to Clearance of Therapeutic Antibody

Abstract: Many chronic inflammatory diseases are treated by administration of “biological” therapies in terms of fully human and humanized monoclonal antibodies or Fc fusion proteins. These tools have widespread efficacy and are favored because they generally exhibit high specificity for target with a low toxicity. However, the design of clinically applicable humanized antibodies is complicated by the need to circumvent normal antibody clearance mechanisms to maintain therapeutic dosing, whilst avoiding development of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 93 publications
0
2
1
Order By: Relevance
“…The liver is vital in human immunity 28 . Interestingly, a recent study also suggested that the liver plays an important role in regulating antibody titers 29 . However, we failed to identify ALT and AST levels as independent factors associated with seropositivity IgG against SARS‐CoV‐2 in PLWH in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…The liver is vital in human immunity 28 . Interestingly, a recent study also suggested that the liver plays an important role in regulating antibody titers 29 . However, we failed to identify ALT and AST levels as independent factors associated with seropositivity IgG against SARS‐CoV‐2 in PLWH in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…It appears that the antibody profiles to vaccination prevention in older individuals respond ineffectively and decline easily owing to immunosenescence and comorbidities 38 ; therefore, regular boost shots and shortened vaccine intervals might help. Intriguingly, we found AST and TC as independent factors associated with the positive proportion of NAb to BA.4/5 and IgG anti‐RBD antibodies, suggesting the central function of the liver in regulating antibody production 39,40 …”
Section: Discussionmentioning
confidence: 75%
“…Hepatobiliary excretion was associated with considerable liver retention for both RevTMs (Figure 9F). The IgG4-based RevTM showed the highest liver uptake, possibly due to its Fc portion (53,54).…”
Section: Pet Imaging Of Revtms In Tumor-bearing Micementioning
confidence: 99%